2017
DOI: 10.1089/lap.2016.0295
|View full text |Cite
|
Sign up to set email alerts
|

Greater Omental Milky Spot Examination for Diagnosis of Peritoneal Metastasis in Gastric Cancer Patients

Abstract: The laparoscopic exploration could make a preliminary diagnosis of peritoneal metastasis via serosal layer invasion detection. For further analyses, cytological examinations of greater omental milky spots were more sensitive than exfoliative cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Surgical resection is the major treatment for GC patient (4); however, patients in advanced gastric cancer with peritoneal metastasis, a non-curable factor, showed poor prognosis (5). Peritoneal metastasis (PM) primary occurs in T4 stage (6,7). Accurate evaluation of PM status in GC patients is essential for treatment decision and prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical resection is the major treatment for GC patient (4); however, patients in advanced gastric cancer with peritoneal metastasis, a non-curable factor, showed poor prognosis (5). Peritoneal metastasis (PM) primary occurs in T4 stage (6,7). Accurate evaluation of PM status in GC patients is essential for treatment decision and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate evaluation of PM status in GC patients is essential for treatment decision and prognosis. It was found that some biomarkers and histopathological factors (e.g., T, N staging, Greater Omental Milky Spot, and Troponin I2) could predict PM status in GC (7,8), but they just provided low prediction or were merely available postoperatively. Preoperative assessment of PM can provide useful information for performing adjuvant treatment and avoid unnecessary surgical resection, thus contributing to pretreatment decision.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the pathological stage of the tumor was not included in this study. Diagnosing GC in stages T3–T4, patients are more likely to have a higher risk of PM ( 47 ). Thirdly, the deviation of the results may be caused by irregular lesions.…”
Section: Discussionmentioning
confidence: 99%